Summary of taxonomy changes ratified by the International Committee on Taxonomy of Viruses from the Plant Viruses Subcommittee, 2025 - Rubino, L.; Abrahamian, P.; An, W.; Aranda, M.A.; Ascencio-Ibañez, J.T.; Bejerman, N.; Blouin, A.G.; Candresse, T.; Canto, T.; Cao, M.; Carr, J.P.; Cho, W.K.; et al. (2025)
In March 2025, following the annual International Committee on Taxonomy of Viruses (ICTV) ratification vote, newly proposed taxa were added to those under the mandate of the Plant Viruses Subcommittee. In brief, 1 new order, 3 new families, 6 new genera, 2 new subgenera and 206 new species were created. Some taxa were reorganized. Genus Cytorhabdovirus in the family Rhabdoviridae was abolished and its taxa were redistributed into three new genera Alphacytorhabdovirus, Betacytorhabdovirus and Gammacytorhabdovirus. Genus Waikavirus in the family Secoviridae was reorganized into two subgenera (Actinidivirus and Ritunrivirus). One family and four previously unaffiliated genera were moved to the newly established order Tombendovirales. Twelve species not assigned to a genus were abolished. To comply with the ICTV mandate of a binomial format for virus species, eight species were renamed. Demarcation criteria in the absence of biological information were defined in the genus Ilarvirus (family Bromoviridae). This article presents the updated taxonomy put forth by the Plant Viruses Subcommittee and ratified by the ICTV.